Different Dispatches - Humphries, David T. (Literary Criticism and Cultural Theory, 2006)
In "Different Dispatches", David Humphries brings together in a new way a diverse group of well-known American writers of the inter-war period including: Willa Cather, Sherwood Anderson, Ernest Hemmingway, Zora Neale Hurston, James Agee and Robert Penn Warren. He demonstrates how these writers engage journalism in creating innovative texts that address mass culture as well as underlying cultural conditions. The book will be of interest to readers approaching these well-known authors for the first time or for scholars grappling with larger issues of cultural production and reception.